POLA PERSUKUAN BAHASA ALORES DI PULAU ALOR NUSA TENGGARA TIMUR - Adhiti, Ida Ayu Iran (LPPM IKIP PGRI Bali, 2018)
In relation with the effort to establish and develop the language in Nusa Tenggara Timur region especially in Alor Country, it need deep observation on language phenomena, especially about syllable pattern. The observation analyses one of the local languages in Alor country firstly Alores language that is also called Alurung language, located in Kepala Burung seasone. Based on the clarification of spreading area and the scope of speaker. The Alores language is the biggest language in Alor island.                 The vocabularies that are analysed use a list of 200 vocabularies of Swadesh with the word pattern having one word syllable two word syllables, three word syllables, and four word syllables.The pattern of syllable of Alores language are one syllable, two syllables, three syllables, and four syllable. Words with one syllable having pattern CVC are found the most used firstly 18 lexicons. Word having two syllable with the pattern CVCV are 58 lexicon, are the most used compared to the other syllable patterns. Words having three syllables with the pattern CVCVCV are found the most used, firstly 12 lexicon. Words having four syllable with the pattern CVCVCVCV, VCVCCVVV, VCVCVCVC, and VCVCVV are found one lexicon each.